Not aid, but trade - an application of ARDL bound test for Pakistan economy - Mazher Muhammad Ahmad; Jauhari Dahalan (Goodwood Publishing, 2020)
Purpose: Our research study aimed to analyze the statement of the proverb 'Not-Aid, but-Trade,' for the economy of Pakistan over 1970-2018 based on time-series data collected from the World Development Indicators - World Bank. Research Methodology: Through evaluation of the theoretical and empirical literature, we estimate the influence of official development assistance, trade openness, foreign direct investment, inflation, and gross capital formation on the gross domestic product of Pakistan. To accomplish the required concerns, we implied the Unit-Root test, and the Autoregressive Distributed Lag Model Bound analysis. Results: No significant relationship revealed between inflation and official development assistance. In contrast, the openness of trade and foreign direct investment shows a significant positive relationship with the gross domestic product of Pakistan. Similarly, gross capital formation has a negative but significant connection with the gross domestic product of Pakistan. For the short-run period, trade openness, foreign direct investment, and inflation impart to a positive and significant relationship; however, gross capital formation presents a negative but significant linking with gross domestic product. Limitations: Our study covers the Pakistan economy time-series data over the 1970-2018 period. Contribution: Our study is helpful for the Pakistani economic policy formation, particularly useful for academics and researchers to understand the basic concept related to 'not-aid but-trade' philosophy. Keywords: GDP, ODA, Trade, GCF, Inflation